Clinical and molecular profile of a new series of patients with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome: Inconsistent correlation between forkhead box protein 3 expression and disease severity - Gambineri, Eleonora; Perroni, Lucia; Passerini, Laura; Bianchi, Lucia; Doglioni, Claudio; Meschi, Franco; Bonfanti, Riccardo; Sznajer, Yves; Tommasini, Alberto; Lawitschka, Anita; Junker, Anne; Dunstheimer, Desiree; et al. (Journal of allergy and clinical immunology, 2008)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is an autoimmune genetic disorder caused by mutation of the forkhead box protein 3 gene (FOXP3), a key regulator of immune tolerance. We sought to provide clinical and molecular indicators that facilitate the understanding and diagnosis of IPEX syndrome. In 14 unrelated affected male subjects who were given diagnoses of IPEX syndrome based on FOXP3 gene sequencing, we determined whether particular FOXP3 mutations affected FOXP3 protein expression and correlated the molecular and clinical data. Molecular analysis of FOXP3 in the 14 subjects revealed 13 missense and splice-site mutations, including 7 novel mutations. Enteropathy, generally associated with endocrinopathy and eczema, was reported in all patients, particularly in those carrying mutations within FOXP3 functional domains or mutations that altered protein expression. However, similar genotypes did not always result in similar phenotypes in terms of disease presentation and severity. In addition, FOXP3 protein expression did not correlate with disease severity. Severe autoimmune enteropathy, which is often associated with increased IgE levels and eosinophilia, is the most prominent early manifestation of IPEX syndrome. Nevertheless, the disease course is variable and somewhat unpredictable. Therefore genetic analysis of FOXP3 should always be performed to ensure an accurate diagnosis, and FOXP3 protein expression analysis should not be the only diagnostic tool for IPEX syndrome.